Clinical and Physiological Correlates of Irritability in Depression: Results from the Netherlands Study of Depression and Anxiety - Verhoeven, Floor E. A.; Booij, Linda; Van der Wee, Nic J. A.; Penninx, Brenda W. H. J.; Van der Does, A. J. Willem (Depression Research and Treatment, 2011)
Objective. Irritable and nonirritable depressed patients differ on demographic and clinical characteristics. We investigated whether this extends to psychological and physiological measures. Method. We compared irritable and nonirritable unipolar depressed patients on symptomatology, personality, and (psycho)physiological measures (cortisol, cholesterol, and heart rate variability). Symptomatology was reassessed after one year, and we also compared depressed patients who were irritable or non-irritable at both time points (Irr++ versus Irr−−). Results. Almost half (46%; N=420) of the sample was classified as irritable. These patients scored higher on depression severity, anxiety, hypomanic symptoms, and psychological variables. No differences were observed on physiological markers after correction for depression severity. The same pattern was found when comparing Irr++ and Irr−− groups. Conclusion. Irritable and non-irritable depressed patients differ on clinical and psychological variables, but not on the currently investigated physiological markers. The clinical relevance of the distinction and the significance of the hypomanic symptoms remain to be demonstrated.